Tetrafluorobromates for Urban Mining of Noble Metals: A Case Study on Iridium Metal. Issue 28 (2nd August 2013) - Ivlev, Sergey; Woidy, Patrick; Kraus, Florian; Gerin, Ivan; Ostvald, Roman
Abstract: Iridium is used as a hardening agent in several alloys and as a new‐generation catalyst. Therefore, its recycling is a high‐priority challenge. The reactions of various tetrafluorobromates MBrF4 (M = K, Rb, Cs) and M′(BrF4 )2 (M′ = Ba) with Ir metal were investigated in order to transform the latter to an easily soluble form to facilitate the further recovery of the noble metal. The compositions of the obtained products were determined, corresponding reaction schemes are suggested, and proper conditions for the reactions were established. Abstract : The reactions of iridium metal with alkali and alkaline earth metals was studied by using X‐ray powder diffraction and thermal analyses. The investigations show that the respective hexafluoridoiridates(IV) are obtained.